CPW-Fed disc-loaded monopole array antenna with integrated PIN diode switches - Kamarudin, Muhammad Ramlee; Hall, P. S.; Colombel, F.; Himdi, M. (2007)
A switched beam disk-loaded parasitic monopole antenna array with coplanar waveguide (CPW) feeding systems with integrated PIN diode switches is described. The measured gain of the antenna in the direction of the open-circuited parasite element is in the range of 5.1 dBi to 5.6 dBi. It was confirmed that by changing the control current to the switches, the main beam direction of the antenna can be switched in the azimuthal plane. The reflection coefficient for all four configurations is matched at 2.45 GHz.